Bargaining power and local heroes - Ulrich Heimeshoff; Gordon J. Klein (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2013)
Bargaining Power of retailers is an important aspect of discourse in many industrialized countries, including Germany, Portugal, the UK, and the USA. In Germany the Federal Cartel Office argues that strong bargaining power of retailers presents danger for workable competition in the market. Furthermore, significant bargaining power on the retailer side is often assumed a priori without further investigation. Based on a treatment effect study using difference-in-differences techniques we show, that even small suppliers can have superior bargaining power against retailers depending on their shares on local markets. We do not argue that retailers have no bargaining power at all, but we want to show, that the division of bargaining power between the two sides of the markets varies from product to product and is also a dynamic phenomenon which changes over time. As a result, the a priori assumption of bargaining power of retailers can be very misleading.
Keywords: 330